Globalization and the jobs ladder - Carl Davidson; Fredrik Heyman; Steven J. Matusz; Fredrik Sjöholm; Susan Chun Zhu (Research Institute of Industrial Economics (IFN), 2018)
Globalization might affect the mix of jobs available in an economy and the rate at which workers gain skills. We develop a model in which firms differ in terms of productivity and skills and use the model to examine how globalization affects the wage distribution and the career path of workers as they move up the jobs ladder. There are two types of skills that determine a worker's productivity in the model: the ability to work with the appropriate technology and the ability to facilitate international commerce. Workers imperfectly acquire these skills on the job. Firms cannot costlessly observe the skills embodied in a worker but can observe each potential recruit's employment history. In equilibrium, firms self-select into groups that use different networks to fill vacancies. Our results indicate that although falling trade costs may result in greater wage inequality, if trade costs are initially high, it can also lead to a wider path up the jobs ladders and less time spent in entry level jobs. The key assumptions and predictions are confirmed in data on recruitments and job mobility in Sweden.
Keywords: F10; F20; J30; 330; Job Ladders; Globalization; Wages; Inequality; Export